An Anti-Phishing Approach that Uses Training Intervention for Phishing Websites Detection - Alnajim, A.; Munro, M. (2009 Sixth International Conference on Information Technology: New Generations, 2009)
Phishing scams have become a problem for online banking and e-commerce users. This paper proposes and evaluates a novel anti-phishing approach that uses training intervention for phishing websites detection (APTIPWD). The proposed approach helps users to make correct decisions in distinguishing phishing and legitimate Websites. It brings information to end-users and helps them immediately after they have made a mistake in order to recognize phishing Websites by themselves. This paper reports that there is a significant positive effect of using the new approach in comparison with an old approach of sending anti-phishing tips by email. The new approach is better in helping users properly judge legitimate and Phishing Websites.